Trends in anthropogenic ammonia emissions in China since 1980: A review of approaches and estimations - Chen, Jianan; Cheng, Miaomiao; Krol, Maarten; de Vries, Wim; Zhu, Qichao; Liu, Xuejun; Zhang, Fusuo; Xu, Wen (Frontiers in Environmental Science, 2023)
Ammonia (NH3) emissions from intensive anthropogenic activities is an important component in the global nitrogen cycle that has triggered large negative impacts on air quality and ecosystems worldwide. An accurate spatially explicit high resolution NH3 emission inventory is essential for modeling atmospheric aerosol pollution and nitrogen deposition. However, existing NH3 emission inventories in China are still subject to several uncertainties. In this review we firstly summarize the widely used methods for the estimate of NH3 emissions and discuss their advantages and major limitations. Secondly, we present aggregated data from ten NH3 emission inventories to assess the trends in total anthropogenic NH3 emissions in China over the period 1980–2019. Almost emission estimates reported that NH3 emissions in China have doubled in the last four decades. We find a substantial differences in annual total NH3 emissions, spatial distributions and seasonal variations among selected datasets. In 2012, the median emission (Tg yr−1) and associated minimum-maximum ranges are 12.4 (8.5_17.2) for total emission, 9.9 (8.1_13.8) for agriculture, 0.3 (0.2_1.0) for industry, 0.4 (0.2_1.1) for residential and 0.1 (0.1_0.3) for transport and other emission of 1.5 (0.3_2.6). In general, peak emissions occur in summer but in different months, the higher NH3 emission intensities are concentrated in the NCP area, and in eastern and south-central China but distinct regional discrepancy among selected datasets. Finally, we made an analysis of the reasons and levels of difference in NH3 emission estimates with recommendations for improvement of China’s NH3 emission inventory.